Spatial relationship between population shrinkage and land development in northeast China - Wang, Xueqin; Hu, Jiacheng; Zhao, Shen; Hu, Rui (Frontiers in Environmental Science, 2025)
IntroductionAnalyzing the features of population shrinkage and land development, as well as the spatial coordination relationship between population and land, has reference value for optimizing the allocation of land resources in areas with shrinking populations.MethodsThis paper analyzed space–time features of population shrinkage and land-use intensity (LUI) in northeast China, which is a typical shrinking area in China. Furthermore, the correlation coefficient measurement method and coupling coordination model were applied to explore the spatial relationship between population shrinkage and land development.ResultsThe main results show that (1) Both the total population and the labor force in northeast China shrank between 2010 and 2020, while the contribution of the labor force to the whole population remained at a level above the national average throughout the period. (2) Significant differences existed in population shrinkage types among county-level units, including absolute shrinkage type, labor-growth shrinkage type, labor-loss growth type, and absolute growth type, indicating that the change trend of the labor population and that of the total population are not exactly consistent. (3) The land-use intensity of county-level units has gradually increased despite varying degrees of population loss from 2000 to 2020, presenting a paradoxical phenomenon of population loss and land spatial expansion. (4) In most county-level units, the population changes are negatively correlated with the land-use intensity change and have an uncoupled coordination relationship with it. (5) The match between population and landuse is stronger in regional central cities and shows a spatial characteristic of decreasing from the center to the periphery.DiscussionThis study helps reveal the relationship between population and land in typical areas of China with shrinking populations, laying a certain foundation for seeking ways to achieve coordinated development between humans and land.